Effect of Flexion and Rotation on Measures of Coronal Alignment after TKA - Kannan, Arun; Hawdon, Gabrielle; McMahon, Stephen John (The Journal of Knee Surgery, 2012)
Attainment of a neutral mechanical axis is one of the primary goals in total knee arthroplasty (TKA). The accuracy of the procedure is evaluated by measuring the hip-knee-ankle angle (HKAA) on long leg radiographs. Rotation of the lower limb and knee flexion could possibly affect the HKAA measured on plain radiographs. In this study, a TKA was performed on a saw-bone model of the lower limb. Long leg radiographs from the femoral head to the ankle were obtained after sequentially varying the alignment of the knee model in 5-degree increments of flexion and rotation, from 0 to 20 degrees. Flexion or external rotation alone, up to 20 degrees changed the HKAA by no more than 1 degree. A combination of flexion and external rotation progressively altered the HKAA. The HKAA was altered by 5 degrees at a combination of 15- or 20-degree flexion and 20-degree external rotation. While flexion or external rotation alone had little effect on the HKAA, a combination of the two altered it substantially.
Keywords: knee arthroplasty; coronal alignment; knee flexion; knee rotation